Penilaian Maturity Level Sistem Manajemen Kinerja Pendidikan Tinggi Berdasarkan Critical Success Factors - Aulia Sri Dharma Nova; Henmaidi Henmaidi; Dicky Fatrias; Irna Ekawati (Politeknik ATI Padang, 2022)
Higher education institution is an organization whose role is to produce professional, qualified and competitive human resources. Thus, it is required to be able to implement a good performance management system by building a common understanding of the goals to be achieved and how they can be achieved, as well as the approaches needed to manage and develop resources to improve individual, team and organizational performance. In order to be able to implement a performance management system effectively, adequate initial information is needed to determine the current level of organizational maturity as a basis for further improvement. In this study, a model of the maturity level of a performance management system was developed which was adapted to the form of higher education organization. The results show that the maturity level of the Polytechnic ATI Padang's performance management system is at level three, which means the organization already has clear and integrated policies and guidelines in carrying out its education and management processes followed by the use of up-to-date technology. The development and management of resources have been identified based on needs, as well as the formation of a participatory culture in most work units. Improved technology infrastructure is needed to enable effective use of data and the development of HR skills and knowledge regarding performance management systems so as to increase awareness of the influence of individual performance on the overall performance of the institution.